2014
DOI: 10.1186/1471-2466-14-45
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and long-term survival of pulmonary arterial hypertension in the Czech Republic: a retrospective analysis of a nationwide registry

Abstract: BackgroundPulmonary arterial hypertension (PAH) is a severe and progressive disease characterized by increased pulmonary vascular resistance, ultimately leading to right heart failure and death. Epidemiological data from national registries are growing worldwide, but are still unavailable in Eastern Europe.MethodsA PAH registry was initiated in January 2007 using a nationwide network of echocardiographic centers and four diagnostic centers that specialize in PAH. All patients aged above 18 years, diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 17 publications
1
47
2
2
Order By: Relevance
“…Depending on the registry, the proportions range from 39% to 61% for IPAH, 11-28% for CTD-PAH, 10-20% for CHD-PAH and 5-10% for portopulmonary hypertension-PAH [4,7,9,12]. These findings do not appear to have changed over time.…”
Section: Pah Aetiologymentioning
confidence: 56%
See 4 more Smart Citations
“…Depending on the registry, the proportions range from 39% to 61% for IPAH, 11-28% for CTD-PAH, 10-20% for CHD-PAH and 5-10% for portopulmonary hypertension-PAH [4,7,9,12]. These findings do not appear to have changed over time.…”
Section: Pah Aetiologymentioning
confidence: 56%
“…The PH registry of the UK and Ireland found a significant increase in the age of patients over the period from 2001 to 2009 [6]. Similarly, data from the Czech registry in [2000][2001][2002][2003][2004][2005][2006][2007] showed that patients diagnosed during 2007 were 10 years older than the population diagnosed prior to 2007 [7].…”
Section: Proportion Of Male and Female Patientsmentioning
confidence: 99%
See 3 more Smart Citations